2015
DOI: 10.1007/s00894-015-2606-4
|View full text |Cite
|
Sign up to set email alerts
|

The DFT study on the reaction between benzaldehyde and 4-amine-4H-1,2,4-triazole and their derivatives as a source of stable hemiaminals and schiff bases. Effect of substitution and solvation on the reaction mechanism

Abstract: Reaction mechanism for the benzaldehyde (ald) and 4-amine-4H-1,2,4-triazole (4at) has been investigated at the DFT (B3LYP)/6-31+G(d) computational level. Three transition states (TS) have been identified. The TS1 corresponds to hydrogen transfer from the NH2 group to the C = O bond and nucleophillic attack of the carbon atom from the aldehyde group on the nitrogen atom from the NH2 group in 4at. The result of this reaction is the hemiaminal molecule. The TS2 characterises an internal rearrangement of the benze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 38 publications
0
13
2
Order By: Relevance
“…The potential applications of the method cover the determination of the mechanisms of reactions belonging to organic as well as inorganic chemistry as done in recent studies. 79,81,82,122,136,143,146,[167][168][169][170][171][172][173] We believe that the approach proposed here can thus be useful not only in a variety of circumstances to provide quantitative insights into the nature of chemical reactivity and for the modelling of reaction mechanism, based on the electron density transfers but also it should become a powerful tool in the chemical education of undergraduate students because our theoretical findings can serve as a general guideline for the study and analysis of the chemical structure and reaction mechanisms. Our understanding of the chemical structure and reactivity is usually built up from and dependent upon such intuitive concepts as atom in molecule, chemical bond, lone pair, Lewis structure, etc.…”
Section: Discussionmentioning
confidence: 92%
“…The potential applications of the method cover the determination of the mechanisms of reactions belonging to organic as well as inorganic chemistry as done in recent studies. 79,81,82,122,136,143,146,[167][168][169][170][171][172][173] We believe that the approach proposed here can thus be useful not only in a variety of circumstances to provide quantitative insights into the nature of chemical reactivity and for the modelling of reaction mechanism, based on the electron density transfers but also it should become a powerful tool in the chemical education of undergraduate students because our theoretical findings can serve as a general guideline for the study and analysis of the chemical structure and reaction mechanisms. Our understanding of the chemical structure and reactivity is usually built up from and dependent upon such intuitive concepts as atom in molecule, chemical bond, lone pair, Lewis structure, etc.…”
Section: Discussionmentioning
confidence: 92%
“…[45] The values for the water elimination process reported for other reactions seem to match roughly the range between the values found for path 1 (42.3 kcal mol -1 ) and path 2 (55.5 kcal mol -1 ), cf. [42] Contrary to some other reactions where the hemiaminal [44] forms or the amine and aldehyde reactants [43] seem to be the structures of the lowest energy on potential energy surface, the most thermodynamically preferable form of the presently studied system is the macrocycle product, at 0K forming the post-reactive hydrogen bonded complexes 1(CP)···H 2 [42] Contrary to some other reactions where the hemiaminal [44] forms or the amine and aldehyde reactants [43] seem to be the structures of the lowest energy on potential energy surface, the most thermodynamically preferable form of the presently studied system is the macrocycle product, at 0K forming the post-reactive hydrogen bonded complexes 1(CP)···H 2 …”
Section: Computational Detailsmentioning
confidence: 96%
“…Non-templated condensation of 2,6-diformylpyridine (DFP) and racemic trans-1,2-diaminocyclopentane (DACP), or racemic trans-1,2-diaminocyclohexane (DACH). [59,60] In particular, quantum chemical topology methods applied to the reaction between benzaldehyde and 4-amine-4H-1,2,4triazole indicated that the nucleophilic addition to form CN covalent bond is preceded by the creation of OH bond, [42,43] contrary to what is typically observed for other systems. While the second stage, consisting of some conformational changes, seems to be rather trivial, the hemiaminal synthesis and water elimination steps are more complicated as both involve N···H···O proton transfer and either NC bond formation (the former process) or CO bond dissociation (the later one).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations